Basophil activation test: food challenge in a test tube or specialist research tool?. Issue 1 (15th March 2016) - Santos, Alexandra F.; Lack, Gideon
Abstract: Oral food challenge (OFC) is the gold‐standard to diagnose food allergy; however, it is a labour and resource‐intensive procedure with the risk of causing an acute allergic reaction, which is potentially severe. Therefore, OFC are reserved for cases where the clinical history and the results of skin prick test and/or specific IgE do not confirm or exclude the diagnosis of food allergy. This is a significant proportion of patients seen in Allergy clinics and results in a high demand for OFC. The basophil activation test (BAT) has emerged as a new diagnostic test for food allergy. With high diagnostic accuracy, it can be particularly helpful in the cases where skin prick test and specific IgE are equivocal and may allow reducing the need for OFC. BAT has high specificity, which confers a high degree of certainty in confirming the diagnosis of food allergy and allows deferring the performance of OFC in patients with a positive BAT. The diagnostic utility of BAT is allergen‐specific and needs to be validated for different allergens and in specific patient populations. Standardisation of the laboratory methodology and of the data analyses would help to enable a wider clinical application of BAT.